The case for free markets. (8th November 2021) - Philippon, Thomas
Abstract: I argue that our failure to nurture free markets is partly responsible for the negative attitudes of many citizens towards capitalism. In doing so, I also revisit the broader argument that the old Washington consensus is dead.